Pelatihan Canva Untuk Peningkatan Kualitas Kegiatan Belajar Mengajar di SDN 06 Kota Bengkulu - Dinda Khairunisa; Tri Astuti Rahayu; Anies Fitria Junensi; Ramadhan Adesyaputra (Gayaku Publisher, 2024)
Public Elementary School 06 Bengkulu City is a school located in Jalan Nusyirwan Zainul, Kampung Bali, Kecamatan Teluk Segara, Bengkulu City. The school is utilized for the implementation of Canva training to enhance the quality of teaching and learning activities at SDN 06 Bengkulu City. SD Negeri 06 Bengkulu has 12 teachers. The primary issue during the internship (Field Work Practice) is the limited knowledge of teachers about Canva. Therefore, during the internship program, we took steps through a work program in the form of Canva Training to improve the quality of teaching and learning activities at SDN 06 Bengkulu City. This training provides Canva presentation skills, enabling teachers to create engaging and easily understandable learning materials. Teachers will learn the basics of Canva, its features, and interactive learning through Canva. Not all teachers are familiar with Canva and have a deep understanding of it. In addressing this issue, we took various steps to enable teachers to discuss and solve problems encountered in creating instructional media. We then provided an opportunity for teachers to practice creating instructional media with the guidance of an instructor.